Stress Ibu Selama Kehamilan Merupakan Risiko Persalinan Prematur - Hasda Hasda; Fajar Kurniawan (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2024)
Under-five mortality in Southeast Sulawesi province is estimated to be more than 50% due to the risk of LBW, asphyxia, pneumonia, diarrhea and congenital abnormalities. The incidence of LBW with the most cases was found in South Konawe District with 266 infants out of a total of 5,796 births. The purpose of the study was to determine the causative factors of preterm labor at the South Konawe District Hospital, this research method is quantitative with an observational approach using a Case Control Study design, this research was conducted from February to March 2023 at the South Konawe District Hospital with a total sample of 116 respondents. The sampling technique for the condition group (Premature Labor) carried out in this study used a probability sample, namely Simple random sampling. The results of the study showed that stress has a risk of 11.22 times the incidence of preterm labor in South Konawe District Hospital. It is concluded that stress in pregnant women is a risk factor for preterm labor.